1990
DOI: 10.1021/jm00168a028
|View full text |Cite
|
Sign up to set email alerts
|

Design of peptidomimetic .delta. opioid receptor antagonists using the message-address concept

Abstract: Highly selective nonpeptide ligands with potent delta opioid receptor antagonist activity have been developed using the message-address concept. This approach envisaged the delta opioid receptor to contain two major recognition subsites; a message subsite which recognizes the pharmacophore, and an address subsite that is unique for the delta receptor type and confers selectivity. The message and address components of the delta-selective enkephalins were postulated to be Tyr1 and Phe4, respectively, with Gly2-G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
254
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 283 publications
(266 citation statements)
references
References 5 publications
11
254
1
Order By: Relevance
“…In an attempt to improve the selectivity of the delta opioid indolomorphinans naltrindole (1) and oxymorphindole (2), 1 we previously showed that the corresponding 4-hydroxy-3-methoxyindolomorphinans (such as 3 and 4) had widely differing selectivity over mu opioid receptors, with some being very selective and others possessing poor selectivity, 2 consistent with studies by others with similarly substituted opioids. 3 The differences in affinity at delta receptors and selectivity over mu receptors compared to the indolomorphinans may be due to the presence of the 4-hydroxyl, the lack of a 3-hydroxyl, or the fact that modeling studies showed that opening the 4,5-bridge caused a shift in the relative position of the indole.…”
mentioning
confidence: 53%
“…In an attempt to improve the selectivity of the delta opioid indolomorphinans naltrindole (1) and oxymorphindole (2), 1 we previously showed that the corresponding 4-hydroxy-3-methoxyindolomorphinans (such as 3 and 4) had widely differing selectivity over mu opioid receptors, with some being very selective and others possessing poor selectivity, 2 consistent with studies by others with similarly substituted opioids. 3 The differences in affinity at delta receptors and selectivity over mu receptors compared to the indolomorphinans may be due to the presence of the 4-hydroxyl, the lack of a 3-hydroxyl, or the fact that modeling studies showed that opening the 4,5-bridge caused a shift in the relative position of the indole.…”
mentioning
confidence: 53%
“…The early Fischer indole synthesis of 2c with cyclohexanone 30) afforded an angular 3H-benz 31) The same reactions from cyclopentanone 32) and naltrexone, 33) a cyclohexanone derivative, with 2c, however, afforded linear 1H-benz[f]indole derivatives 7 and 8 as a sole product, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Solutions of -conotoxin GVIA and -agatoxin TK (Alomone Labs, Jerusalem, Israel) were prepared at their final concentration in HEPES buffer on the day of use. Based on the literature, the lowest concentration tested for each opioid antagonist was selective for one receptor subtype (Pelton et al, 1986;Portoghese et al, 1990;Bonner et al, 1997;Ananthan et al, 1998). The calcium channel blockers were used at concentrations reported to be effective and selective in blocking VDCCs in DRG neurons in vitro (Cardenas et al, 1997;Endoh and Suzuki, 1998;Formenti et al, 1998).…”
Section: Methodsmentioning
confidence: 99%